Coaching doctoral students – a means to enhance progress and support self-organisation in doctoral education. Issue 2 (3rd May 2016) - Godskesen, Mirjam; Kobayashi, Sofie
ABSTRACT: In this paper we focus on individual coaching carried out by an external coach as a new pedagogical element that can impact doctoral students' sense of progress in doctoral education. The study used a mixed-methods approach in that we draw on quantitative and qualitative data from the evaluation of a project on coaching doctoral students. We explore how coaching can contribute to the doctoral students' development of a broad set of personal competences and suggest that coaching could work as a means to engender self-management and improve relational competences. The analysis of the participants' self-reported gains from coaching show that doctoral students experience coaching as an effective method to support the doctoral study process. This study also provides preliminary empirical evidence that coaching of doctoral students can facilitate the doctoral study process so that the doctoral students experience an enhanced feeling of progress and that they can change their study behaviour in a positive direction. The study discusses the difference between coaching and supervision, for instance power imbalances and contrary to earlier research into coaching of doctoral students this study indicates that coaching can impact the supervisor–student relationship in a positive way.